(3CSGSjGJ GdGbJUGO GdfbOj hGdeUQaj (B/s - (3YhV Gddg, RjfHs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2003)
(3GdfbhO hGdfXGe GdfbOj, GdeDSSGJ GdfbOjI hGdeGdjI, GdfbhO hGdeJZjQGJ GdGbJUGOjI(B.s
Keywords: (3GdHfhc(B- (3GdLhGfH GdGbJUGOjIs; (3GdSjGSI GdfbOjIs; (3GdfbhO(B- (3GdLhGfH GdGbJUGOjIs